Prototipe Green Internet Technology Guna Mendukung Infrastruktur Desa Pintar - Nurchim Nurchim; Afu Ichsan Pradana (Politeknik Negeri Batam, 2019)
The internet has become one of the supporting infrastructures for the successful implementation of the smart village. In Indonesia, many village governments have provided public internet access points in the village area. However, the implementation of this access point has not been able to reach all rural areas due to geographical constraints and the availability of electricity. This study aims to make a prototype of an internet access point with solar power, also known as Green Internet Technology. This prototype is done by using a Design-Based Research (DBR) approach which consists of six steps including (1) focusing, (2) understanding, (3) defining, (4) understanding, (5) building, (5) building and (6) tests. The prototype Green Internet Technology has 3 main parts including (1) solar power systems, (2) internet access point systems and (3) solar monitoring systems. Test results in the real environment that the solar power system and internet access point can work 24 hours a day. But going forward, solar monitoring systems need to be reviewed, especially in the stability of the performance of current and voltage sensor devices.